Forecasting Oil price and Volatility - Yu, Man Tao (2009)
Commodities prices play a crucial role in commodity-related investments, strategic planning, and affect the economy. Fluctuations in commodity prices affect the decision making by producers and consumers. Within the commodity products, crude oil is the central source of energy supply. The continuous rise in oil price since 2002 has caused public concerns of higher inflation rate for different countries. In July 2008, crude oil price has rise to a historic price US$147/barrel, and dropped to US$33/ barrel at the end of 2008. The high increase in the oil price has brought an concern of shrinking of world economy. The ability to accurately forecast the prices of commodities are therefore an important concern in both policy and finance area.